Impairment of rat tooth eruption in pups born to mothers exposed to chronic stress during pregnancy - Fontanetti PA; DeLucca R; Mandalunis PM; Vermouth NT (2019)
Objective: Tooth eruption is a multifactorial process in which bone tissue plays a prevailing role. In this study we evaluated the bone overlying the developing tooth germ and the degree of tooth eruption of the first mandibular molar in pups born to mothers subjected to constant light during pregnancy. Design: Pregnant rats were divided into two groups: mothers chronically exposed to a 12:12 light/light cycle (LL) from day 10 to 20 of pregnancy and controls (C) maintained on a 12:12 h light/dark cycle. Pups from each group were euthanized at the age 3 or 15 days. Buccolingually oriented sections of mandibles were stained with haematoxylin?eosin or for histochemical detection of tartrate resistant acid phosphatase (TRAP). The histomorphometric parameters evaluated were bone volume, number of osteoclasts, TRAP+ bone surface, number of TRAP+ and TRAP osteoclasts per mm2 and degree of tooth eruption (mm). Results: It was found an increase in bone volume (LL: 58.14 4.24 vs. C: 32.31 2.16; p < 0.01) and a decrease in the number of osteoclasts (LL: 3.5 0.65 vs. C: 8.03 1.31; p < 0.01) and TRAP+ cells (LL: 0.84 0.53 vs. C: 8.59 1.26; p < 0.01) in 3-day-old pups born to LL-exposed mothers. These observations are consistent with the decrease in the degree of tooth eruption observed in 15-day-old experimental pups (LL: 0.605 0.05 vs. C: 0.342 0.02; p < 0.0001). Conclusion: Our results suggest that chronic constant light applied as a pre-natal stressor impairs the resorptive capacity of osteoclasts involved in the formation of the eruption pathway and consequently the degree of tooth eruption.